GAMBARAN KEPUASAN PASIEN RAWAT JALAN DALAM MENERIMA PELAYANAN BPJS KESEHATAN DI PUSKESMAS BLAHBATUH I GIANYAR - I Gede Abdi Sarya Permana; Komang Menik Sri Krisnawati; Kadek Eka Swedarma (Coping: Community of Publishing in Nursing, 2020)
Health is a basic human need to be able to live worthy and productive, so it needed to provide health services, namely health social services agency which is aligned with the goal to access quality health services. Each person will do the various ways to get a good treatment, included health services such as hospitals and health center to provide the quality of health service so it will lead to the patients satisfaction. Research Objective to know the patients satisfaction of health social services agency participants of outpatient service in health center of Blahbatuh I Gianyar. This research was kind of deskriptif with cross sectional approach. Sample taken by purposive sampling as many 84 respondents. Research instrument was questioner. The results of the tangible dimension study were 20 patients (20%) in the very satisfying category, 71 patients (71%) in the satisfying category, and 9 patients (9%) in the unsatisfactory category. The reliability dimension was very satisfying because of 27 patients (27%) and as many as 73 patients (73%). The dimensions of patient responsiveness were very satisfying as many as 27 patients (27%), satisfying 67 patients (67%), and satisfying 6 patients (6%). The assurance dimension is very satisfying as many as 20 patients (20%) and satisfies as many as 80 patients (80%). The empathy dimension is very satisfying as many as 21 patients (21%) and satisfying as many as 79 patients (79%). It can be concluded that the dominant respondents in the satisfying category are dimensions of tangible, reliability, responsiveness, assurance, and empathy.